Answer:
= 2x²( 2x+ 1) + 2x
or
= 2x (2x² + x + 1)
Explanation:
Given in the question two functions,
f ( x ) = 9x³ + 2x² − 5x + 4
g ( x ) = 5x³ − 7 x + 4
To find,
f ( x ) − g ( x )
Substitute each functions
= 9x³ + 2x² − 5x + 4 - ( 5x³ − 7 x + 4 )
Remove parentheses
= 9x³ + 2x² − 5x + 4 - 5x³ + 7 x - 4
Combine like terms and add them up
= 4x³ + 2x² + 2x
Factorise
= 2x²( 2x+ 1) + 2x
or
= 2x (2x² + x + 1)
So the final answer in factored form is 2x²( 2x+ 1) + 2x or 2x (2x² + x + 1)
This can't be further factorise because answer will be in complex numbers